3D Inkjet Printing of Biomaterials with Solvent‐Free, Thiol‐Yne‐Based Photocurable Inks - Michael Kainz; Stephan Haudum; Elena Guillén; Oliver Brüggemann; Rita Höller; Heike Frommwald; Tilo Dehne; Michael Sittinger; Disha Tupe; Zoltan Major; Gerald Stubauer; Thomas Griesser; et al. (Macromolecular Materials and Engineering, 2024)
Abstract 3D inkjet printing is a fast, reliable, and non‐contact bottom–up approach to printing small and large models and is one of the fastest additive manufacturing technologies available. These attributes position inkjet printing as a promising tool for the additive manufacturing of biomaterials, for example, tissue engineering scaffolds. However, due to the stringent technical rheological requirements of current inkjet technologies, there is a lack of photopolymer resins suitable for the inkjet printing of biomaterials. Hence, a novel ink engineered for 3D piezoelectric inkjet printing of biomaterials is designed and developed. The novel resin leverages a biodegradable amino acid phosphorodiamidate matrix copolymerized with a dialkyne ether to modulate the viscosity. Copolymerization with commercially available thiols facilitates the photochemical thiol‐yne curing reaction. The ink exhibits optimal viscosity, eliminating the need for solvents, as well as reliable jetting and sufficiently swift curing kinetics. Furthermore, the formulation is successfully demonstrated in an industrial inkjet printhead. Notably, the resulting materials have low cytotoxicity and, hence, have significant promise in advancing the applications of 3D inkjet printing of biological scaffolds.